Control of film morphology by folding hydrogen-bonded oligo(p-phenylenevinylene) polymers in solution - Jonkheijm, Pascal; Duren, Jeroen Karolus Johannes van; Kemerink, Martijn; Janssen, René A. J.; Schenning, Albert; Meijer, Ernst Willem (Macromolecules, 2006)
The film morphology of π-conjugated oligomers has been controlled by self-assembly in solution. To this end supramolecular hydrogen-bonded systems of oligo(p-phenylenevinylene) (OPV) carrying ureido-s-triazine hydrogen-bonding groups are used. Neutron scattering experiments in dodecane solutions show that columnar stacks are formed. Films with thicknesses on the order of 100 nm are made that have a supramolecular organization resembling the organization present in solution. Uniform rodlike morphological domains range over several hundreds of nanometers as shown by atomic force microscopy. The rodlike morphology of the OPVs was also preserved when blended with a C60 derivative, producing stable photovoltaic devices.